Pelatihan Pajak Dalam Upaya Peningkatan Pemahaman Praktik PPN Untuk Koperasi Bagi Anggota INKOPAD - Herawaty, Vinola; Daeli, Florus; Aulia Oktaviani, Ayu; Nasyrah Noor, Ice (Jurnal Pengabdian kepada Masyarakat Nusantara, 2023)
Cooperatives function and have a role in building and increasing the business potential and capabilities of members and the community. However, in reality the management of cooperatives in Indonesia is still not optimal, this is partly due to the lack of knowledge of cooperative partners on tax regulations and cooperative tax administration, as well as the large number of cooperative management who are incompetent and lack socialization regarding tax regulations. Failure to comply with tax obligations will certainly result in fines and administrative sanctions which should be avoided by each agency. Therefore, in an effort to increase understanding of tax practices within cooperatives, it is necessary to have competency-based training activities for cooperative members. The Faculty of Economics and Business (FEB) of Trisakti University in collaboration with the Indonesian Army Cooperative Main (INKOPAD) makes this happen in the form of training activities for the community. This training aims to increase understanding and competence in the practice of Value Added Tax (VAT) in cooperative activities. The method of counseling and training activities is used as a solution to the problems of existing partners. After this training, cooperative members’ understanding of VAT practices in cooperative activities has increased.